Solubility of high-value compounds in ethyl lactate: Measurements and modelling - Marina S. Manic (2012)
(Solid + liquid) equilibria of binary mixtures containing high-value compounds and ethyl lactate were studied. Using the gravimetric method, the solubility of various solutes such as caffeine, vanillic acid, ferulic acid, caffeic acid and thymol in ethyl lactate was measured as a function of temperature over the range of (298.2 to 343.2) K, at atmospheric pressure. The differences in solubility of a given solute in water-saturated and dry ethyl lactate were observed. The deviation of these binary systems from ideal mixture behaviour was discussed. In order to understand the solubilization process, melting properties of pure solutes were determined by differential scanning calorimetry (DSC). The solubility data obtained were represented using UNIQUAC and UNIFAC-based models as well as with the Cubic-Plus-Association (CPA) equation of state. The results of the modeling indicate that these models are the appropriate tools for representing the solubility behaviour of various solutes in ethyl lactate.